The Stress Cost of Children - Hielke Buddelmeyer; Daniel S. Hamermesh; Mark Wooden (Institute for the Study of Labor (IZA), 2015)
We use longitudinal data describing couples in Australia from 2001-12 and Germany from 2002-12 to examine how demographic events affect perceived time and financial stress. Consistent with the view of measures of stress as proxies for the Lagrangean multipliers in models of household production, we show that births increase time stress, especially among mothers, and that the effects last at least several years. Births generally also raise financial stress slightly. The monetary equivalent of the costs of the extra time stress is very large. While the departure of a child from the home reduces parents' time stress, its negative impacts on the tightness of the time constraints are much smaller than the positive impacts of a birth.
Keywords: J13; J20; 330; time use; children; demographic economics